equations1111092

# equations1111092 - Equations v xf = v xi ax t f t i x f = x...

This preview shows page 1. Sign up to view the full content.

v xf = v xi + a x t f t i ( ) v yf = v yi + a y t f t i ( ) x f = x i + 1 2 v xi + v xf ( ) t f t i ( ) y f = y i + 1 2 v yi + v yf ( ) t f t i ( ) x f = x i + v xi t f t i ( ) + 1 2 a x t f t i ( ) 2 y f = y i + v yi t f t i ( ) + 1 2 a y t f t i ( ) 2 v xf 2 = v xi 2 + 2 a x x f x i ( ) v yf 2 = v yi 2 + 2 a y y f y i ( ) a y = g ˆ y g = 9.80 m s 2 = 32.2 ft s 2 cos θ = x h sin θ = y h tan θ = y x h = x 2 + y 2 Δ x = x f x i v x , avg = x f x i t f t i a avg = v f v i t f t i v x = lim Δ t 0 Δ x Δ t a x = lim Δ t 0 Δ v x Δ t az 2 + bz + c = 0 z = b ± b 2 4 ac 2 a Σ F = m a F G = Gm 1 m 2 r 2 = mg f S max = μ S N f k = μ k N F x = kx a r = v 2 / r v = v v o r = r v o t K = 1 2 m v 2 W = F cos φ d
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern